2014
DOI: 10.1590/1807-3107bor-2015.vol29.0011
|View full text |Cite
|
Sign up to set email alerts
|

Surface roughness and wear of resin cements after toothbrush abrasion

Abstract: Increased surface roughness and wear of resin cements may cause failure of indirect restorations. The aim of this study was to evaluate quantitatively the surface roughness change and the vertical wear of four resin cements subjected to mechanical toothbrushing abrasion. Ten rectangular specimens (15 × 5 × 4 mm) were fabricated according to manufacturer instructions for each group (n = 10): Nexus 3, Kerr (NX3); RelyX ARC, 3M ESPE (ARC); RelyX U100, 3M ESPE (U100); and Variolink II, Ivoclar/Vivadent (VL2). Init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Karimzadeh et al 31 and Jager et al 32 mentioned that filler quantity in resin composites could be a factor that allows improving their surface microhardness. 2 , 33 , 34 In that sense, Rizzante et al, 33 in their study, observed that bulk fill–type nanohybrid resins achieved superior surface microhardness values compared to conventional resins with less filler. 11 , 12 As is known, Tetric N-Ceram Bulk Fill resin composite (76 wt%; 54 vol%) has lower inorganic filler and filler content than Filtek Bulk Fill (76.5 wt%; 58.4 vol%) and Opus Bulk Fill (76.5 wt%; 58.4 vol%) resins.…”
Section: Discussionmentioning
confidence: 96%
“…Karimzadeh et al 31 and Jager et al 32 mentioned that filler quantity in resin composites could be a factor that allows improving their surface microhardness. 2 , 33 , 34 In that sense, Rizzante et al, 33 in their study, observed that bulk fill–type nanohybrid resins achieved superior surface microhardness values compared to conventional resins with less filler. 11 , 12 As is known, Tetric N-Ceram Bulk Fill resin composite (76 wt%; 54 vol%) has lower inorganic filler and filler content than Filtek Bulk Fill (76.5 wt%; 58.4 vol%) and Opus Bulk Fill (76.5 wt%; 58.4 vol%) resins.…”
Section: Discussionmentioning
confidence: 96%
“…However, the extrinsic staining is exposed to the oral environment and can be worn by toothbrushing in the long term [9,21]. Most of the abrasive simulation using toothbrushing evaluated the surface roughness quality [2,3,18,22] instead of wear rate [21,23,24]. In addition, limited data are available regarding the effect of toothbrushing on the staining layer of CAD/CAM ceramics over time [3,9,18,21].…”
Section: Discussionmentioning
confidence: 99%
“…The staining layer on the feldspathic ceramic is suggested to be removed after 10−12 years of simulated toothbrushing. This result could be improved if a glaze layer is applied over the stain, protecting it from wear [2,9,21,23,33]. A previous study evaluated the influence of load and brushing time on the surface roughness and gloss of a composite resin and two leucite-based ceramics.…”
Section: Discussionmentioning
confidence: 99%
“…All the cycles were performed at 37 ± 1ºC and 4.5 cycles/s. ( 16 ) Every 2 minutes, 0.4mL of slurry (toothpaste and distilled water at a ratio of 1:2) was automatically injected and the toothbrushes were changed after every 5000 brushing cycles. After brushing, specimens were stored immersed in water at 60ºC in absence of light during 24 hours ( 14 , 15 ).…”
Section: Methodsmentioning
confidence: 99%